The Bildungsroman in the emancipatory conception of the colonized Jewish subject in the work of Albert Memmi - Barbosa, Daiani da Silva (Cadernos de Língua e Literatura Hebraica, 2023)
This paper analyzes the work The Salt Statue, by the French-Tunisian writer Albert Memmi in dialogue with the theory on the Bildungsroman, understood as "novel of formation", and the field of Cultural Studies. In this way, we insert the work in this literary genre but, at the same time, we present it as a subversion of the classical models by deviating the hero's trajectory from the standard plot in paradigmatic works of self-formation. Thus, in addition to the formation of the subject's personality, we will discuss the character's Jewish heritage and his condition as a colonized person by the French empire, as well as the tradition-modernity relationship in the neocolonial context of the twentieth century.